Views regarding use of complementary therapies for acute respiratory infections: Systematic review of qualitative studies. (May 2020) - Willcox, Merlin; Donovan, Emily; Hu, Xiao-Yang; Elboray, Shereen; Jerrard, Naomi; Roberts, Nia; Santer, Miriam
Highlights: We found 22 qualitative studies about complementary therapies for acute respiratory infections. Participants mostly thought CAM is an acceptable option for treatment of mild ARIs. This depends on beliefs about the illness (cause, severity). Use of CAM depends on its availability and beliefs about its efficacy and safety. Participants wanted trustworthy advice about which CAM treatments are best. Abstract: Background: Unnecessary antibiotic prescribing and use are most common for uncomplicated acute respiratory infections (ARIs). Some Complementary and Alternative Medicine (CAM) treatments have evidence of effectiveness for symptom relief and could be used instead of antibiotics. Aim: To understand views of the general public and health professionals regarding use of CAM for uncomplicated ARIs. Design and Setting: Systematic review and thematic synthesis of qualitative studies. Method: We systematically searched MEDLINE, EMBASE, AMED, COREHOM, CINAHL, Dissertation and theses global and Web of Science Core Collection. We included studies which reported qualitative data on the use of CAM for uncomplicated ARIs where participants were either patients or parents of patients, health professionals or the general public. Analysis followed thematic synthesis. Results: Twenty-two studies were included from four high-income and ten low-and-middle income countries; almost all focussed on non-White populations. Nineteen concerned parents' treatment of ARIs in their children. In all settings, treatment decisions were influenced by beliefs about the illness (cause, severity), beliefs about treatments (efficacy, safety), availability of treatments and of trustworthy advice. Participants mostly thought CAM is an acceptable option for treatment of mild ARIs but felt that they need trustworthy advice on which treatments to use and when. Conclusion: Treatment decisions depend on beliefs about the illness and treatments, availability of treatments and advice. CAM treatments appear to be acceptable to people from many different settings as a possible alternative to antibiotics for mild ARIs. There is a need for reliable, evidence-based advice on which treatments to use.